Differences in Mortality Rates of Gunshot Victims: The Influence of Neighborhood Social Processes - Magee, Lauren A. (Homicide studies, 2023)
Firearm violence is considered a public health crisis in the United States. Firearm violence spatially concentrates within neighborhoods and is associated with community factors; however, little is understood about the geographic differences in gunshot wound mortality and associated neighborhood social processes. Applying a public health approach through the Haddon’s Matrix, the results demonstrate systematic differences in social and physical features associated with gunshot mortality. These findings have important implications to improve neighborhood physical and social conditions, police transporting gunshot victims, and police-public health partnerships to improve data collection on nonfatal shootings and shots fired.